Effect of PCSK9 inhibitors on pulse wave velocity and monocyte-to-HDL-cholesterol ratio in familial hypercholesterolemia subjects: results from a single-lipid-unit real-life setting - Scicali, Roberto; Di Pino, Antonino; Ferrara, Viviana; Rabuazzo, Agata Maria; Purrello, Francesco; Piro, Salvatore (Acta diabetologica, 2021)
Aims Subjects with familial hypercholesterolemia (FH) are characterized by an increased amount of low-density lipoprotein cholesterol (LDL-C) that promotes a continuous inflammatory stimulus. Our aim was to evaluate the effect of PCSK9-i on inflammatory biomarkers, neutrophil-to-lymphocyte ratio, monocyte-to-high-density lipoprotein ratio (MHR), and on early atherosclerosis damage analyzed by pulse wave velocity (PWV) in a cohort of FH subjects. Methods In this prospective observational study, we evaluated 56 FH subjects on high-intensity statins plus ezetimibe and with an off-target LDL-C. All subjects were placed on PCSK9-i therapy and obtained biochemical analysis as well as PWV evaluation at baseline and after six months of PCSK9-i therapy. Results After six months of add-on PCSK9-i therapy, only 42.9% of FH subjects attained LDL-C targets. As expected, a significant reduction of LDL-C (− 49.61%, p < 0.001) was observed after PCSK9-i therapy. Neutrophil count (NC) and MHR were reduced by PCSK9-i (-13.82% and -10.47%, respectively, p value for both < 0.05) and PWV significantly decreased after PCSK9-i therapy (− 20.4%, p < 0.05). Finally, simple regression analyses showed that ∆ PWV was significantly associated with ∆ LDL-C ( p < 0.01), ∆ NC and ∆ MHR ( p value for both < 0.05). Conclusions In conclusion, PCSK9-i therapy significantly improved lipid and inflammatory profiles and PWV values in FH subjects; our results support the positive effect of PCSK9-i in clinical practice.